Experimental comparison of corrosion behavior of pure magnesium, iron coated magnesium and hydroxyapatite coated magnesium in Hanks Basic salt solution for cardiovascular application. (12th June 2019) - Vignesh, R; Sakthinathan, G
Abstract: Biomaterials (BM) research is one of the emerging fields, and much research has been carried out towards the development of new and improved BMs. The latest development in the field of biomaterials is to develop biodegradable BMs for different applications. Many attempts have been carried out with alloys of Magnesium (Mg) and Iron (Fe), and even though Mg and Fe are found to be suitable materials, each has its limitations. Problem with Mg is its high rate of degradation while Fe has a very slow degradation rate. Hydroxyapatite (HaP) is one of the naturally occurring materials found in human bones, and many research publications have discussed the utilization of HaP. In the present study, Mg has been considered as the base material, and the effect of coating Fe and HaP on Mg substrate has been studied via immersion test in Hanks Basic salt solution (HBSS). Fe and HaP were coated on pure Mg substrate using physical vapor deposition technique (PVD). Pure Mg was used as control while Fe coated and HaP coated Mg were compared against it for mass loss and corrosion rate in HBSS for 20 days. Electrochemical corrosion test was carried on a three-electrode test rig. Fe coated Mg showed very high degradation as compared to pure Mg samples due to the formation of galvanic cells. Corrosion rate for Fe coated Mg was observed as high as (42.88 ± 1.39) mm yr −1, and it was verified with the electrochemical test, while pure Mg specimen had a maximum corrosion rate of (5.8 ± 0.35)mm yr −1 . HaP coated samples showed low corrosion rate as compared to pure Mg and Fe coated Mg. The maximum corrosion rate in Hap coated specimen was observed to be (5.55 ± 0.95) mm yr −1 . PVD is a very good method for coating HaP and Fe on Mg substrate, but galvanic cell formation in case of Fe coating inhibits its usage while nonreactive passive layer of HaP proved to very effective in reducing the corrosion rate of Mg.